Addressing Women's Health Care Needs During Pediatric Care - Rachel N. Caskey; Sarah E. Olender; Alejandra Zocchi; Cara J. Bergo; Keriann H. Uesugi; Sadia Haider; Arden S. Handler (Mary Ann Liebert, 2021)
Objective: To determine if the use of a simple self-administered Postpartum Questionnaire for Mothers (PQM) at the well-baby visit (WBV) increased the proportion of women who received health care and contraception by 6 months postpartum (PP). Methods: This was a single-site, system-level, intervention. Women were recruited from the pediatric clinic when presenting with their infants for a 2-month WBV. During phase 1 of the study, a control group was enrolled, followed by an 8-week washout period; then enrollment of the intervention group (phase 2). During phase 2, the PQM was administered and reviewed by the pediatrician during the infant's visit; the tool prompted the pediatrician to make a referral for the mother's primary or contraceptive care as needed. Data were collected at baseline and at 6 months PP, and additional data were extracted from the electronic medical record. Results: We found that PP women exposed to the PQM during their infant's WBV were more likely to have had a health care visit for themselves between 2 and 6 months PP, compared with the control group (relative risk [RR] 1.66, [confidence interval (CI) 0.91?3.03]). In addition, at 6 months PP, women in the intervention group were more likely to identify a primary care provider (RR 1.84, [CI 0.98?3.46]), and more likely to report use of long-acting reversible contraception (LARC) (RR 1.24, [CI 0.99?1.58]), compared with women in the control group. Conclusion: A simple self-administered PQM resulted in an increase in women's receipt of health care and use of LARC by 6 months PP. Clinical Trial Registration: Use of a reproductive life planning tool at the pediatric well-baby visit with postpartum women, NCT03448289.